A Synodal Church in Mission—Ethical Implications: Perspectives from Tamilnadu - Sahayaraj Stanley (Asian Horizons, 2025)
The synodal Church is marching towards the mission of fulfilling the dreams of the Kingdom of God. As we trace the history, one can chalk out three distinct models of this missionary Church. The first model is of a ‘conquering’ Church. In the past, the Church had conquered foreign lands and cultures and planted itself in those unfamiliar territories. Next came the ‘intellectual’ model in which the Church wanted to enter into a highbrow, cognitive dialogue with the local cultures, in the hope of eventually winning people’s minds and hearts. The third model is of the ‘prophetic’ Church. Roughly, basing its tenets on liberation theology, the focus of this third model is a commitment to an all-inclusive liberation. The synodal Church’s three ‘inner’ ethical implications, and three ‘outer’ ethical ramifications are further elaborated. For a fruitful ‘inner’ ethical orientation, it is argued that this synodal Church needs conversion and needs to believe in the ‘good news’ of the Lord and help people grow in mature faith. Other ethical ‘outer’ challenges include tackling the menace of clericalism and removing the curse of casteism. Ultimately, the synodal Church needs to herald a prophetic approach with a total societal transformation. These ethical approaches may further sharpen and crystallize if the Church and its faithful carefully read the signs of the times and act accordingly.